Bridging as Metaphor- A Systems Thinking Approach for Exploring Transboundary Risk - Locklear, Kathleen (Archives of Business Research, 2022)
This paper provides a novel approach for understanding transboundary risk, including ‘grand challenges’ such as climate change. Discussion begins with an exploration of the origins of transboundary risk as a byproduct of globalization. Thereafter, the concept of ‘bridging’ is used in order to conceptualize the spread of transboundary risk across traditional physical boundaries, including geographic borders. Building upon prior theory, systems thinking and complexity are used as conceptual lenses for understanding the dynamics of transboundary risk. Scenario planning is offered as a means for envisioning and addressing the challenges presented by transboundary risk. The result of this discussion is a holistic, systems view of transboundary risk which stands in contrast to traditional, reductionist perspectives of risk. As such, the paper concludes by proposing a set of epistemological questions that emerge as a result of this shift.